Compensatory health beliefs in women in the first, second and third trimester of pregnancy - Magdalena Mazur-Skupowska; Katarzyna Byrka (Health Psychology Report, 2023)
Background Compensatory health beliefs may serve as one of many self-regulatory strategies that individuals employ to maintain healthy lifestyles. Past research with samples from a general population has shown, however, that compensatory beliefs are ineffective in this regard and may even lead to inaction in future health-related behaviors such as eating healthily or being active. To better understand this phenomenon, in the present study, changes in compensatory health beliefs regarding various life domains were examined in a group of pregnant women.